PERANCANGAN PLAZA LAMONGAN DENGAN TEMA ARSITEKTUR NEO VERNAKULAR - Dhiah Agustina Qahar; Moh. Agus Tiyo Rifky (DEARSIP : Journal of Architecture and Civil, 2023)
Plaza is a certain area consisting of one or several shops that are erected vertically orhorizontally in a city, which are sold or leased to business actors or managed independently toconduct goods trading activities. The use of neo vernacular architectural themes aims to preservelocal elements formed empirically by a tradition which then more or less undergoes renewaltowards a more modern or advanced work without putting aside local traditional values. Buildingsthat are more varied, flexible, innovative, dynamic and diverse, both in material and technologyare able to achieve visual targets, rooms and outdoor spaces that achieve harmony in the Plazadesign. And also this concept in principle pays attention to normative, cosmological principles,the role and local culture in people's lives and the harmony between buildings, nature and theenvironment. The whole building has 3 zoning, namely the private zone, the semi-public zone, andthe public zone.